Does Gender Diversity on Boards Influence Stock Market Liquidity? Empirical Evidence from the Tunisian Market - Abidi, Ilyes; Nsaibi, Mariem (International Journal of Economics and Financial Issues, 2022)
The aim of this paper is to study the effect of the gender diversity in boardrooms on the liquidity of the shares. To do this, we selected a sample made up of Tunisian banks listed over the period 1998-2018, and we used the two-step least squares method (2SLS). The results of this work show a significant and positive relationship between the gender diversity on the boards of directors and the liquidity of the shares of Tunisian banks. However, the results of this investigation suggest that the presence of at least one woman on the board positively affect the liquidity of the shares. This relationship becomes more meaningful when there is more than one woman on the board, but their presence will be normalized if they occupy at least three positions.